The thermal degradation of epoxy resins (5) - Bishop, D. P. (College of Aeronautics, 1968)
A summary of work carried out between March 1968 and August 1968 on the resin hardener systems DDIVEP274, PA/EP274, LY558/HT973, EP274/Synolide 960, and CY175/HT907/DY065.